Septicemic melioidosis: A forensic autopsy case report - Atif Shamsudin; Heo Chong Chin; Ahmad Hafizam Hasmi; Hapizah Mohd Nawawi (Wolters Kluwer Medknow Publications, 2018)
We report a 27-year-old male from Kuwait who died due to melioidosis, and the diagnosis was achieved after the deceased underwent postmortem examination at the Forensic Department, Kuala Lumpur Hospital. While the disease is endemic in Southeast Asia and Northern Australia, human melioidosis infection has yet been reported in Kuwait. He was initially diagnosed as acute gastroenteritis at a private clinic before being found dead at a hotel in Kuala Lumpur. The autopsy revealed positive findings of Burkholderia pseudomallei in the deceased's brain, lung, liver, and spleen as well as in the blood and cerebrospinal fluid culture. The deceased's death highlights the importance of early accurate diagnosis, the common manifestations, and the need of effective antibiotic treatment of septicemic melioidosis in high prevalent areas.